Música rural brasileira: hibridismos, modernidade, conflitos e adaptações (1929 – 1990) - Dias, Alessandro Henrique Cavichia (2021)
Brazilian rural music undoubtedly occupies a prominent place in national cultural production, as well as in the phonographic and cultural industry. Thus, to understand the formation of the aesthetic fields of the genres popularly known as "caipira" and "sertanejo" is to understand Brazil in the 20th century. This work arises from the observations made around the transformations undergone by Brazilian rural music throughout the twentieth century, specifically between the years 1929 and 1990. In 1929, the first recordings take place, under paid material by Cornélio Pires, of the then known country music, later being converted to country music in the 1950s, 1960s and 1970s, and in the last two, it became romantic country musicians. Thus, it is worth questioning how these transformations of rural music take place, which often contribute to drawing a sinuous border between the modern and the traditional, and then understand that the formatting of this border is inserted in an intense modernizing process composed of hybridities, conflicts and adaptations made through a dense symbolic struggle between interpreters, the public and the cultural industry.